2022
DOI: 10.1111/pedi.13367
|View full text |Cite
|
Sign up to set email alerts
|

Childhood type 1 diabetes is associated with abnormal bone development

Abstract: Objective: To describe bone mineral density (BMD), bone structure, and fracture prevalence in adolescents with type 1 diabetes (T1D) and explore their associations with glycemic control and microvascular complications.Research design and methods: Cross sectional study of 64 adolescents (38 males) with T1D duration >10 years who underwent dual-energy X-ray absorptiometry (DXA), peripheral quantitative computed tomography (pQCT), fracture survey, plantar fascia thickness, and microvascular complications assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
(168 reference statements)
0
0
0
Order By: Relevance
“…In another study, Madsen et al [25] examined OC, P1NP, and CTX levels in 99 individuals with T1DM 3 months after diagnosis and three times at 6-month intervals and showed that bone destruction increased and bone turnover decreased in the first year after T1DM diagnosis. Vora et al [26] evaluated dual-energy X-ray absorptiometry (DXA), peripheral quantitative computed tomography (pQCT), plantar fascia thickness, and microvascular complications in 64 adolescents with a duration of T1DM > 10 years and found site-specific low bone density in the upper and lower extremities. Eckert et al [27] compared T1DM patients aged ≤ 25 years with a history of bone fracture with T1DM patients without a history of bone fracture and reported that bone fractures were more common at an earlier age in T1DM patients than in the general population and that the risk of fracture was associated with HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Madsen et al [25] examined OC, P1NP, and CTX levels in 99 individuals with T1DM 3 months after diagnosis and three times at 6-month intervals and showed that bone destruction increased and bone turnover decreased in the first year after T1DM diagnosis. Vora et al [26] evaluated dual-energy X-ray absorptiometry (DXA), peripheral quantitative computed tomography (pQCT), plantar fascia thickness, and microvascular complications in 64 adolescents with a duration of T1DM > 10 years and found site-specific low bone density in the upper and lower extremities. Eckert et al [27] compared T1DM patients aged ≤ 25 years with a history of bone fracture with T1DM patients without a history of bone fracture and reported that bone fractures were more common at an earlier age in T1DM patients than in the general population and that the risk of fracture was associated with HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%